STRES DAN KOPING MAHASISWA KEPERAWATAN SELAMA PEMBELAJARAN DARING DI MASA PANDEMIK COVID-19 - Herna Angelica; Evelyn Hemme Tambunan (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Traditional learning has shifted into online learning by the policy to prevent the transmission of the Covid-19 virus. Online learning is a learning pattern using internet technology networks. The online learning system is a new learning system in Indonesia and can cause stress. Coping is a response to changes in the learning system. The research objective was conducted to describe the level of stress and coping in students of the Faculty of Nursing, Universitas Advent Indonesia. Using descriptive quantiative research, the population of the study were all students of the academic and profession stage of bachelor nursing program. Convenience sampling method utilized and, 157 respondents filled out the validated DDAS-42 and coping strategy questionnaires. The questionnaires were distributed via google form and the data were analyzed using a frequency distribution to describe the level of stress and coping utilization in online learning. The results showed that most of the students were at normal stress levels, a small proportion at mild, moderate, severe levels and very little at very severe levels. Most of the students utilized emotion- focused coping and a small proportion utilized problem-focused coping or equally utilized the two coping strategies. Educators and students should be aware of stres and effective coping management.